The Navier-Stokes equations : a classification of flows and exact solutions - Drazin, P. G.; Riley, N. (Norman); Cambridge eBooks; London Mathematical Society (Cambridge : Cambridge University Press, 2006)
The Navier-Stokes equations were firmly established in the 19th Century as the system of nonlinear partial differential equations which describe the motion of most commonly occurring fluids in air and water, and since that time exact solutions have been sought by scientists. Collectively these solutions allow a clear insight into the behavior of fluids, providing a vehicle for novel mathematical methods and a useful check for computations in fluid dynamics, a field in which theoretical research is now dominated by computational methods. This 2006 book draws together exact solutions from widely differing sources and presents them in a coherent manner, in part by classifying solutions via their temporal and geometric constraints. It will prove to be a valuable resource to all who have an interest in the subject of fluid mechanics, and in particular to those who are learning or teaching the subject at the senior undergraduate and graduate levels.
Scope of the book -- Steady flows bounded by plane boundaries -- Steady axisymmetric and related flows -- Unsteady flows bounded by plane boundaries -- Unsteady axisymmetric and related flows.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Navier-Stokes equations; Electronic books